The effect of customer experience on customer loyalty mediated by customer satisfaction and customer trust: (Study on users of PLN mobile application at PLN UP3 Malang) - Mohammad Eryan Saputra; Sumiati Sumiati; Agung Yuniarinto (Journal of Economics and Business Letters, 2023)
Customer experience refers to the internal, subjective response to an interaction with a product or service. Customer loyalty demonstrates customers' deep commitment to resubscribe or make consistent and repeated use of a service or product in the future. Mobile applications can integrate elements of customer experience, customer satisfaction, and customer trust to foster customer loyalty. The Mobile Application Customer Experience (MACE) highlights factors that influence customer experience, particularly in mobile application usage, including ease of use, convenience, customization, timeliness, and enjoyment. In this study, customer experience and customer loyalty are the independent and dependent variables, respectively, with customer satisfaction and customer trust acting as mediating variables. Employing a quantitative approach with explanatory research methods, the study is located at PLN UP3 Malang, and focuses on PLN UP3 Malang customers who have used the PLN Mobile application, with a total of 130 respondents. The results revealed that the variables of customer experience, customer satisfaction, and customer trust have a positive and significant impact on customer loyalty, both directly and indirectly. The mediating variables, customer satisfaction and customer trust, have a positive and significant influence on customer loyalty, as confirmed by mediation tests conducted.